Technology for the Use of Reduced Doses of Diminazene Aceturate for the Treatment of Pet Babesiosis - Khristianovsky , Pavel; Belimenko, Vladislav (KnE Life Sciences, 2021)
Babesiosis (piroplasmosis) is a transmissible parasitic disease, accompanied by fever, anemia, yellowness of the mucous membranes, hemoglobinuria, lost productivity and performance, and with untimely treatment – death of livestock. Therapy to treat livestock babesiosis involves, first of all, the use of anti-babesial drugs. This study aimed the examine the effectiveness of using a reduced diminazene aceturate (DA) dosage against babesiosis in livestock. However, the use of these drugs can cause side effects. The study recommends the use of DA-based drugs against equine babesiosis at a dose of 2.6 mg/kg bodyweight for an active ingredient (AI). With volumetric dosing it is 0.038 cm3 of a 7 % solution per kg bodyweight, rather than 0.05 cm3 per kg bodyweight, as indicated in the instructions. The use of a reduced dose of Batrizin (2.5 and 3.0 mg/kg AI) and Fa.Try.Banil. (2.5 mg/kg AI) to treat experimental babesiosis in dogs had a satisfactory anti-babesial effect in the absence of intoxication. Keywords: diminazene aceturate, babesiosis, parasitic disease